2021
DOI: 10.3389/fmicb.2021.630345
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Lower Respiratory Tract Microbiome and Allergic Respiratory Tract Diseases in Children

Abstract: Similar to those in the upper respiratory tract, there are microbes present in the healthy human lower respiratory tract (LRT), including the lungs and bronchus. To evaluate the relationship between LRT microbiome and allergic respiratory diseases in children, we enrolled 68 children who underwent bronchoscopy from January 2018 to December 2018 in the affiliated hospital of the Capital Institute of Pediatrics. Using the total IgE (TIgE) values, children were divided into two groups: allergy sensitivity (AS) gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Anoxybacillus was one of the most abundant airborne thermophilic bacterial genera in China ( 31 ) that contaminated processed food products, which were not initially considered human colonizers ( 32 ). However, a recent study reported that Anoxybacillus enrichment in the lower respiratory tract might suppress allergies in Chinese children ( 33 ). We revealed that this genus decreased with time independent of AE, suggesting Anoxybacillus to be a transient colonizer of NPM with a potentially protective role in Asian asthmatic children.…”
Section: Discussionmentioning
confidence: 99%
“…Anoxybacillus was one of the most abundant airborne thermophilic bacterial genera in China ( 31 ) that contaminated processed food products, which were not initially considered human colonizers ( 32 ). However, a recent study reported that Anoxybacillus enrichment in the lower respiratory tract might suppress allergies in Chinese children ( 33 ). We revealed that this genus decreased with time independent of AE, suggesting Anoxybacillus to be a transient colonizer of NPM with a potentially protective role in Asian asthmatic children.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pharyngeal colonization of Haemophilus sp. and Streptococcus sp., together with the upper respiratory tract pathogen Moraxella sp., was identified as a risk factor for acute and aggravated allergic asthma episodes among children ( 99 ). Finally, the impact of synergistic infections with respiratory pathogens, such as the influenza A virus and Streptococcus pneumoniae was also implicated to interact with factors associated allergic inflammation to Aspergillus fumigatus .…”
Section: Microecological Factors Associated With Allergic Diseasementioning
confidence: 99%
“…Although several studies have investigated airway or gut microbiota in childhood asthma (Bisgaard et al, 2007;Arrieta et al, 2015;Cui et al, 2015;Teo et al, 2015Teo et al, , 2018Bomar et al, 2018), limited studies examined nasal microbiota in school children and adolescents (Kloepfer et al, 2014;Perez-Losada et al, 2017;McCauley et al, 2019;Zhou et al, 2019), and only two focused on acute exacerbation (AE) (McCauley et al, 2019;Zhou et al, 2019). AE represents a specific window of time of an agitated immune system.…”
Section: Introductionmentioning
confidence: 99%